Negative Immunomodulatory Effects of Type 2 Porcine Reproductive and Respiratory Syndrome Virus-Induced Interleukin-1 Receptor Antagonist on Porcine Innate and Adaptive Immune Functions - Nedumpun, Teerawut; Techakriengkrai, Navapon; Thanawongnuwech, Roongroje; Suradhat, Sanipa (Frontiers in Immunology, 2019)
Impaired innate and adaptive immune responses are evidenced throughout the course of PRRSV infection. We previously reported that interleukin-1 receptor antagonist (IL-1Ra) was involved in PRRSV-induced immunosuppression during an early phase of infection. However, the exact mechanism associated to PRRSV-induced IL-1Ra immunomodulation remains unknown. To explore the immunomodulatory properties of PRRSV-induced IL-1Ra on porcine immune functions, monocyte-derived dendritic cells (MoDC) and leukocytes were cultured with type 2 PRRSV, and the immunological role of IL-1Ra was assessed by addition of anti-porcine IL-1Ra Ab. The results demonstrated that PRRSV-induced IL-1Ra reduced phagocytosis, surface expression of MHC II (SLA-DR) and CD86, as well as downregulation of IFNA and IL1 gene expression in the MoDC culture system. Interestingly, IL-1Ra secreted by the PRRSV-infected MoDC also inhibited T lymphocyte differentiation and proliferation, but not IFN- production. Although PRRSV-induced IL-1Ra was not directly linked to IL-10 production, it contributed to the differentiation of regulatory T lymphocytes (Treg) within the culture system. Taken together, our results demonstrated that PRRSV-induced IL-1Ra downregulates innate immune functions, T lymphocyte differentiation and proliferation, and influences collectively with IL-10 in the Treg induction. The immunomodulatory roles of IL-1Ra elucidated in this study increase our understanding of the immunobiology of PRRSV.